Quality of life: fractionated stereotactic radiotherapy versus enucleation treatment in uveal melanoma patients. Issue 8 (3rd October 2018) - van Beek, Jackelien G.M.; Buitendijk, Gabrielle H.S.; Timman, Reinier; Muller, Karin; Luyten, Gregorius P.M.; Paridaens, Dion; Naus, Nicole C.; Kiliç, Emine
Abstract: Purpose: To report the quality of life and visual functioning in uveal melanoma patients treated with enucleation or fractionated stereotactic radiation therapy (fSRT). Methods: Uveal melanoma (UM) patients treated with fSRT ( n  = 65) or enucleation ( n  = 48) participated in this prospective study. Questionnaires to measure anxiety (State‐Trait Anxiety Inventory), subjective distress (Impact of Event Scale) and quality of life (EORTC‐QLQ‐C30 and National Eye Institute Visual Function Questionnaire (VFQ‐25)) were obtained before treatment and 2, 6, 12, 24, 36 and 48 months after treatment. Results: Less peripheral vision was observed until 3 years (p = 0.026) posttreatment in enucleated patients compared to irradiated patients. From 2 months until 3 years posttreatment irradiated patients increase in role functioning‐score (p = 0.005), while enucleated patients decrease in score (p = 0.012). Regardless of their treatment, for all patients we measured a reduction in physical functioning (p = 0.035), insomnia (p < 0.001) and in state anxiety from pretreatment until 2 years posttreatment (p < 0.001). An increase in pain overall (p = 0.023) and in emotional functioning is observed 1 year posttreatment (p < 0.001). At baseline, patients with metastases (independent of their treatment) have more subjective distress (p = 0.037) than patients without metastases. The mean 'global health score' overall, without effect of time, was 76.4 (SD: 13.6). Conclusion: Enucleated patients had more difficulty working or performing household tasks 2 months posttreatment compared to irradiated patients. Enucleated patients had diminished peripheral vision until 3 years compared to irradiated patients. Overall quality of life is not significantly different between both treatment groups.